Investigation of Different Slot-Pole Combinations of An In-Wheel BLDC Motor for Light Electric Vehicle Propulsion - (:unkn) unknown (IEEE, 2016)
In this study, the optimum design of a BLDC motor which is used for in-wheel light electric vehicle propulsion is presented. The optimisation work is mainly based on different slot-pole numbers which give a substantial performance for that certain application. An outer rotor, 2.5kW, 150V BLDC motor which is widely implemented in light electric vehicle traction is selected. Finite Element Analysis (PEA) is of the target motor design is conducted for various slot-pole combinations. By using the captured design data, the optimised motor is manufactures and tested. The test and simulation results are compared in order to investigate the optimisation approach.